Biogas : Animal Waste That Can be Alternative Energy Source - Haryati, Tuti (Indonesian Animal Sciences Society, 2006)
Biogas is a renewable energy which can be used as alternative fuel to replace fossil fuel such as oil and natural gas . Recently, diversification on the use of energy has increasingly become an important issue because the oil sources are depleting . Utilization of agricultural wastes for biogas production can minimize the consumption of commercial energy source such as kerosene as well as the use of firewood . Biogas is generated by the process of organic material digestion by certain anaerobe bacteria activity in aerobic digester . Anaerobic digestion process is basically carried out in three steps i.e. hydrolysis, acidogenic and metanogenic . Digestion process needs certain condition such as C : N ratio, temperature, acidity and also digester design . Most anaerobic digestions perform best at 32 - 35Â°C or at 50 - 55Â°C, and pH 6 .8 - 8 . At these temperatures, the digestion process essentially converts organic matter in the present of water into gaseous energy . Generally, biogas consists of methane about 60 - 70% and yield about 1,000 British Thermal Unit/ft 3 or 252 Kcal/0.028 m3 when burned . In several developing countries, as well as in Europe and the United States, biogas has been commonly used as a subtitute environmental friendly energy . Meanwhile, potentially Indonesia has abundant potential of biomass waste, however biogas has not been used maximally . Key words : Biogas, renewal energy, anaerobic